Propuesta arquitectónica para un centro de innovación empresarial en Pitalito (Huila) - Quiza Reyes, Andres Mauricio (Universidad Antonio Nariño, 2021)
In the follow-up work of undergraduate thesis for the architecture program, a research work will be carried out, in order to analyze a current problem of a lack of specialized and innovative infrastructure to attend the different activities that the dynamics of tourism and trade in the municipality of Pitalito sue the southern region of the department. Starting from the macro, meso and micro analyzes. Through different investigative methods, to obtain information on why this problem should be solved and from the field of architecture, by proposing the design of an architectural project that meets the plans designed for the municipality by different plans of development, applied by the government and under the different regulations can give a relevant solution and high architectural quality putting into practice the knowledge acquired throughout the career.